Comparison of the Effect of Modified Ward’s and Triangular Flap Design on Periodontium of the Second Molar after Surgical Removal of Mandibular Impacted Third Molar - Patel, Viral; Managutti, Anil; Agrawal, Arvind; Menat, Shailesh; Mahida, Khyati; Patel, Jigar; Managutti, Sunita (Archives of Clinical and Medical Case Reports, 2020)
Background and Objectives: Impacted lower third molar is found in 90% of the general population. Impacted lower third molar surgery may result in complication like pain, swelling, trismus and periodontal health on the distal surface of the adjacent second molar. The aim of this study was to evaluate the effect of flap design on the pain, swelling, trismus, and periodontal health status adjacent to second molar after lower third molar surgery. Materials and Methods: Sixty patients, with an age range of 18-25 years, participated in the present study. They were divided in two groups, each group comprised of 30 patients. In group one triangular flap was used and in group two modified Ward’s flap was used. Post-operatively pain, swelling, trismus was measured on 1st day, 3rd day, and 7th day and periodontal status at 15th days, 1st month, 3rd month and 6th month. Results: No statistically significant differences were found in comparing of pain, swelling, trismus and periodontal status for the between both type of flap design used. Conclusion: It was concluded that the design of mucoperiosteal flap used in surgical removal of impacted mandibular third molar have no effect on the degree of pain, swelling, trismus and periodontal health of adjacent second molar.